2006
DOI: 10.1111/j.1600-6143.2006.01479.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Maturation of Alloreactive CD4-Independent, CD8+ Cytolytic T Cells

Abstract: The goal of this study was to determine the in vivo conditions that promote activation of the (CD4-independent) CD8 + T cell-mediated rejection pathway. We have previously noted that hepatocellular but not islet allografts readily activate this rejection pathway. In the current study, we utilized these two cell transplant models to investigate whether differences in host cell recruitment to the graft site, expression of T-cell activation markers by CD8 + graft infiltrating cells (GICs), and/or development of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…1b). These studies expand upon our previous observations that CD8 ϩ GICs in hepatocyte rejectors express a CTL phenotype (CD8 ϩ CD43 ϩ ) (47) and that the detection of in vivo allocytotoxicity correlates with graft survival status (46,47).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…1b). These studies expand upon our previous observations that CD8 ϩ GICs in hepatocyte rejectors express a CTL phenotype (CD8 ϩ CD43 ϩ ) (47) and that the detection of in vivo allocytotoxicity correlates with graft survival status (46,47).…”
Section: Discussionsupporting
confidence: 64%
“…One study of cardiac allografts reported that host CD4 ϩ T cells are necessary to license dendritic cells for CD8 ϩ T cell activation, CTL function, and CD4-dependent graft rejection (45). However, the development of CTL effectors under CD4-independent conditions in response to allograft tissues such as skin, intestine, and hepatocytes has not been investigated, except for reports by our group showing that the rejection of allogeneic liver parenchymal cells in the absence of CD4 ϩ T cells is accompanied by in vivo cytotoxic effector function (46,47).…”
Section: A Ctivation and Maturation Of Cd8mentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, although we observed a decreased number for the splenic CD4+IFNc -secreting T cells (Th1), but it was not statistically significant. This result suggests that Hmgb1-mediated cytotoxic T cell (CTL) activation could involve both Th1-dependent and independent mechanisms based on the fact that CTLs can be activated without the help of Th1 cells under certain conditions (40)(41)(42). Furthermore, a significantly decreased inflammatory infiltration accompanied by reduced IFNc expression was observed in the allograft after rA-box treatment ( Figures 5 and 6B).…”
Section: Discussionmentioning
confidence: 65%
“…Mice harboring a conditionally targeted mouse survivin gene flanked by two loxP sites (survivin lox/lox ) have been described previously (16,27) (31). Morphometry and islet mass.…”
Section: Methodsmentioning
confidence: 99%